Bullied : the story of an abuse - Alexander, Jonathan (Punctum Books, 2021)
What happens when the defining moment of your life might be a figment of your imagination? How do you understand - and live with - definitive feelings of having been abused when the origin of those feelings won't adhere to a singular event but are rather diffused across years of experience? In Bullied: The Story of an Abuse, Jonathan Alexander meditates on how, as a young man, he struggled with the realization that the story he'd been telling himself about being abused by a favorite uncle as a child might actually just have been a "story" - a story he told himself and others to justify both his lifelong struggle with anxiety and to explain his attraction to other men. Story though it was, Alexander maintains that some form of abuse did occur. In writing that is at turns reflective, analytic, and hallucinatory, Alexander traces what it means to suffer homophobic abuse when such is diffused across multiple actors and locales, implicating a family, a school, a culture, and a politics - as opposed to a singular individual who just happened to be the only openly gay man in young Alexander's life. Along the way, Alexander reflects on Jussie Smollett, drug abuse, MAGA-capped boys, sadomasochism, Catholic priests, cruising, teaching young adult fiction about rape, and a host of other oddly but intimately related topics.